Der Zusammenhang von syntaktischer Variabilität und Textsortenstil in der „Stats= und Gelehrte[n] Zeitung des Hamburgischen unpartheyischen Correspondenten“ (1731) - Schuster, Britt-Marie (Syntaktische Variabilität in Synchronie und Diachronie vom 9. bis 18. Jahrhundert. Akten zum Internationalen Kongress an der Rheinischen Friedrich-Wilhelms-Universität Bonn. 9. bis 12. Juni 2010)
Keywords: Textstilistik

Orientierung an der sich durchsetzenden Norm oder Beibehaltung des individuellen Schreibusus? Beobachtungen zu grafischen Varianten in Tagebüchern um 1900 - Schuster, Britt-Marie (Historische Soziolinguistik des Deutschen X. Historisch-Soziolinguistische Forschungen als Beiträge zur Optimierung der deutschen Sprachgeschichtsschreibung. Internationale Fachtagung Pécs 02.09.–05.09.2010)
Keywords: Kommunikationsgeschichte

Grund und Folge: Beobachtungen zur komplexen Syntax in der Luther-Biographik (1546–1600) - Schuster, Britt-Marie (Geschichte der Gesamtstrukturen vom Althochdeutschen bis zum Frühneuhochdeutschen)
Keywords: Textgrammatik

Eine neue Form politischer Kommunikation? Zu den Video-Podcasts von Angela Merkel - Schuster, Britt-Marie; Lutz, Arnika (Jahrbuch der ungarischen Germanistik 2010 (Die Vernetzung der Welt – neue Medien in Literatur, Sprache und Spracherwerb))
Keywords: Kommunikationsgeschichte

Lernen und Erzählen interdisziplinär. Verhältnisse, Grenzen und offene Fragen - Hartung, Olaf (Lernen und Erzählen interdisziplinär)

Entwicklung eines qualitativen Verfahrens zur Bewertung logistischer Investitionen - Koch, Christian (Ausgewählte Probleme des Logistikmanagements)

Analyse der Anwendbarkeit von Six Sigma als Instrument der Investitionsplanung - Heitmann, Ingmar (Ausgewählte Probleme des Logistikmanagements)

Konzeption eines Logistikcontrollingansatzes zur Abwicklung zeitkritischer Transportvorgänge - Puls, Christoph (Ausgewählte Probleme des Logistikmanagements)

Klassenspezifische und zeitraumbezogene Logistikmengenprognose - Ortgiese, Malte (Ausgewählte Probleme des Logistikmanagements)

Verrechnungspreise in Speditionskooperationen - Opitz, Oliver (Ausgewählte Probleme des Logistikmanagements)

Verrechnungspreise in Speditionskooperationen - Faupel, Christian (Ausgewählte Probleme des Logistikmanagements)

Der Studiengang "Integrierte Sonderpädagogik" an der Universität Bielefeld. - Kottmann, Brigitte (Inklusion in Bildungsinstitutionen)

Food intake of European adolescents in the light of different food-based dietary guidelines: results of the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study - Diethelm, Katharina; Jankovic, Nicole; Moreno, Luis A; Huybrechts, Inge; De Henauw, Stefaan; De Vriendt, Tineke; González-Gross, Marcela; Leclercq, Catherine; Gottrand, Frédéric; Gilbert, Chantal C; Dallongeville, Jean; Cuenca-Garcia, Magdalena; et al. (Public Health Nutrition)
Abstract Objective Since inadequate food consumption patterns during adolescence are not only linked with the occurrence of obesity in youth but also with the subsequent risk of developing diseases in adulthood, the establishment and maintenance of a healthy diet early in life is of great public health importance. Therefore, the aim of the present study was to describe and evaluate the food consumption of a well-characterized sample of European adolescents against food-based dietary guidelines for the first time. Design The HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study is a cross-sectional study, whose main objective was to obtain comparable data on a variety of nutritional and health-related parameters in adolescents aged 12·5–17·5 years. Setting Ten cities in Europe. Subjects The initial sample consisted of more than 3000 European adolescents. Among these, 1593 adolescents (54 % female) had sufficient and plausible dietary data on energy and food intakes from two 24 h recalls using the HELENA-DIAT software. Results Food intake of adolescents in Europe is not optimal compared with the two food-based dietary guidelines, Optimized Mixed Diet and Food Guide Pyramid, examined in this study. Adolescents eat half of the recommended amount of fruit and vegetables and less than two-thirds of the recommended amount of milk (and milk products), but consume much more meat (and meat products), fats and sweets than recommended. However, median total energy intake may be estimated to be nearly in line with the recommendations. Conclusion The results urge the need to improve the dietary habits of adolescents in order to maintain health in later life.

„Ja also, das war ne gute Stunde“. Qualitätsmerkmale von Geschichtsunterricht aus Schülerperspektiven - Meyer-Hamme, Johannes (Geschichte in Wissenschaft und Unterricht 62 (2011) 5/6)

David Hilbert’s Lectures on the Foundations of Physics 1915–1927. Relativity, Quantum Theory and Epistemology, hg. v. Tilman Sauer und Ulrich Majer, in Zusammenarbeit mit Arne Schirrmacher und Heinz-Jürgen Schmidt, Springer: Berlin/Heidelberg 2009 (David Hilbert’s Lectures on the Foundations of Mathematics and Physics, 1891–1933; 5) - Peckhaus, Volker (Mathematical Reviews, MR2569313 (2011c:01023))

Solving the Closest Vector Problem with respect to Lp Norms - Blömer, Johannes; Naewe, Stefanie (arXiv:1104.3720)
In this paper, we present a deterministic algorithm for the closest vector problem for all l_p-norms, 1 < p < ∞, and all polyhedral norms, especially for the l_1-norm and the l_{∞}-norm. We achieve our results by introducing a new lattice problem, the lattice membership problem. We describe a deterministic algorithm for the lattice membership problem, which is a generalization of Lenstra's algorithm for integer programming. We also describe a polynomial time reduction from the closest vector problem to the lattice membership problem. This approach leads to a deterministic algorithm that solves the closest vector problem for all l_p-norms, 1 < p < ∞, in time p log_2 (r)^{O (1)} n^{(5/2+o(1))n} and for all polyhedral norms in time (s log_2 (r))^{O (1)} n^{(2+o(1))n}, where s is the number of constraints defining the polytope and r is an upper bound on the coefficients used to describe the convex body.

Doing Gender: Sprachliche Formen – kommunikative Funktionen – kulturelle Traditionen - Schuster, Britt-Marie (Geschlechterforschung. Theorien, Thesen, Themen zur Einführung)

Zugezogene im Fokus. Eine empirische Studie - Lorenz, Cornelia (Perspektiven der Variationslinguistik. Beiträge aus dem Forum Sprachvariation)

Dada-Zürich. Ästhetische Theorie der historischen Avantgarde. - Bergmeier, Horst

Der souveräne Mensch. Die Anthropologie Heinrich von Kleists. - Müller, Tim